Toxicity studies of 1'-S-1'-acetoxychavicol acetate in rat model / Yasir Osman Ali Abdalla - Yasir Osman , Ali Abdalla (2020)
Natural compounds are the main source of therapeutic molecules for various diseases in this era, and most of the current medicines are derived from plants, microorganisms or animals. Nevertheless, the safety profile of these natural compounds has to be confirmed prior to their medicinal use. 1'-S-1'-acetoxychavicol acetate (ACA), a type of phenylpropanoid extracted from Alpinia conchigera Griff., is one of the natural compounds being investigated for its potential therapeutic purposes. ACA was previously reported to reduce tumour volume in athymic mice at the effective dose of 1.56 mg/kg body weight intraperitoneally and induce apoptotic death of tumour cells through the activation of caspase 3, 9, and 8 in the mitochondrial and Fas-dependent pathways and inactivation of the NF-κB pathway. However, a detailed toxicological profile for ACA has not yet been investigated. Therefore, a toxicity analysis involving intravenous ACA treatments in Sprague-Dawley male/female rats for an acute study of 2, 4 and 6.66 mg/kg doses of body weight for 14 days was conducted. In addition, a sub-acute study with weekly injections of 0.66, 1.33 and 2.22 mg/kg was also performed for 28 days. In these toxicity studies, ACA treatment did not affect behaviour, food/water intake or body weight, and showed insignificant changes in haematology and biochemical parameters or rat mortality. Thus, the LD50 value for ACA is higher than 6.66 mg/kg regardless of the sex of rats. Though there were mild inflammation of the kidneys and lobular hepatitis in sub-acute studies, these were not associated with significant functional adverse effects when compared with control rats. The no-observed-adverse-effect level (NOAEL) for intravenous ACA treatment in 28-day sub-acute studies was 2.22 mg/kg body weight for both male and female rats. The findings show that intravenous ACA treatment at doses tested between 0.66 and 6.66 mg/kg body weight in both acute and sub-acute studies does not result in significant toxicity or death in rats. The present study provides useful information on the safe use of ACA on normal rat model.